Fungi Originating From Tree Leaves Contribute to Fungal Diversity of Litter in Streams - Pirjo Koivusaari; Mysore V. Tejesvi; Mysore V. Tejesvi; Mikko Tolkkinen; Annamari Markkola; Heikki Mykrä; Anna Maria Pirttilä (Frontiers in Microbiology, 2019)
Biomass production and decomposition are key processes in ecology, where plants are primarily responsible for production and microbes act in decomposition. Trees harbor foliar microfungi living on and inside leaf tissues, epiphytes, and endophytes, respectively. Early researchers hypothesized that all fungal endophytes are parasites or latent saprophytes, which slowly colonize the leaf tissues for decomposition. While this has been proven for some strains in the terrestrial environment, it is not known whether foliar microfungi from terrestrial origin can survive or perform decomposition in the aquatic environment. On the other hand, aquatic hyphomycetes, fungi which decompose organic material in stream environments, have been suggested to have a plant-associated life phase. Our aim was to study how much the fungal communities of leaves and litter submerged in streams overlap. Ergosterol content on litter, which is an estimator of fungal biomass, was 5–14 times higher in submerged litter than in senescent leaves, indicating active fungal colonization. Leaves generally harbored a different microbiome prior to than after submergence in streams. The Chao1 richness was significantly higher (93.7 vs. 60.7, p = 0.004) and there were more observed operational taxonomic units (OTUs) (78.3 vs. 47.4, p = 0.004) in senescent leaves than in stream-immersed litter. There were more Leotiomycetes (9%, p = 0.014) in the litter. We identified a group of 35 fungi (65%) with both plant- and water-associated lifestyles. Of these, eight taxa had no previous references to water, such as lichenicolous fungi. Six OTUs were classified within Glomeromycota, known as obligate root symbionts with no previous records from leaves. Five members of Basidiomycota, which are rare in aquatic environments, were identified in the stream-immersed litter only. Overall, our study demonstrates that foliar microfungi contribute to fungal diversity in submerged litter.